Preservation of cultural heritage in Malaysia: An insight of The National Heritage Act 2005 - Mustafa, Nurulhuda Adabiah; Abdullah, Nuraisyah Chua (2013)
The National Heritage Act 2005, the only specific statute on the preservation of cultural heritage is seen to have given a narrow definition and scope of cultural heritage; unlike the broad scope of cultural heritage given by authors. The differentiation between ‘Heritage’ and ‘National Heritage’ in the National Heritage Act 2005 is provided in the Act and due to limited literatures on the legal aspects of the administration of cultural heritage it is timely that the administration of cultural heritage is disclosed. Apart from focusing on the issue of scope of cultural heritage in Malaysia, this paper highlights the significant role of the Commissioner of Cultural Heritage in the Act and emphasises that it should be properly exercised. The absence of archaeological impact assessment and the kind of protection provided to the listed item or objects in the Register are also points highlighted in this paper. The paper concludes with the recommendation that Malaysia should move towards a more active participation in various international conventions relating to preservation of cultural heritage.